Integration of IoT and Blockchain - Mohammad, Arshiya S; Brohi, Muhammad Nawaz; Khan, Iftikhar Alam (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
present, we are in the world of digital revolution. Use of smartphones and internet accelerated due to the impact of the novel Covid-19 virus. The whole world started to turn digital. The industrialization of Internet of Things (IoT) enables more devices to connect and communicate which leads to many data transfer transactions. The architecture of IoT is centralized. The distributed and decentralized architecture of Blockchain can be used to provide secure and scalable transactions of IoT devices. Blockchain is a distributed ledger technology, which provides secure data transactions that cannot be tampered and altered. In this paper, we provide advantages and challenges of integrating IoT and Blockchain. We also provide different architectures and algorithms proposed by researchers to provide secure data transactions. We shall also shed light on the future research directions of integrating Blockchain and IoT.